Kurven - Verstehen - Entwerfen - Berechnen - Darstellen - Degen, Wendelin L. F. (KIT Scientific Publishing, 2018)
The book is intended for a wide range of readers and contains an introduction to various practically relevant aspects of curves with many illustrations: It offers a treatment of the differential geometric basics, of Bézier and B-spline representations, of rational and algebraic curves, and introduces the reader to some special curves, which are important for applications or historical reasons. Proofs requiring more in-depth mathematical knowledge are dispensed with.